Dampak Ekspor dan Impor Terhadap Pertumbuhan Ekonomi di Indonesia - Yoris Daka Pradana Yudha; Muhammad Zaky Khaerul Anwar; De Prabu Dienasti Putra (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This scientific paper aims to determine how exports and imports affect Indonesia's economic growth. The main focus of this study is Gross Domestic Product (GDP) and Indonesia's Economic Growth. The data used comes from the Central Statistics Agency (BPS), and the data collection is carried out by documentation. The results of the study show that exports and imports have an impact on Indonesia's economic growth. In conclusion, if Indonesia exports more goods than imports, state revenues will increase and economic growth will also be better. However, during the pandemic, Indonesia faced many difficulties that affected imports, such as high unemployment rates and declining public income, which reduced people's purchasing power. In addition, the price of imported goods became more expensive. Exports were also hampered because many countries restricted their borders, so that the delivery of export goods was disrupted. These difficulties reduced state revenues, because unemployment increased and domestic production was hampered. All of these problems have an impact on economic growth. To overcome this, the government has made policies to help restore the economy and keep economic growth from slowing down.